2015
DOI: 10.17240/aibuefd.2015.15.0-5000128647
|View full text |Cite
|
Sign up to set email alerts
|

İlkokula Devam Eden Normal Gelişim Gösteren Çocukların Yetersizliği Olan Akranlarına Yönelik Tutumlarının İncelenmesi

Abstract: Bu araştırmanın amacı Edirne il merkezindeki ilkokula devam eden normal gelişim gösteren çocukların yetersizliği olan akranlarına yönelik tutumlarının incelenmesidir. Araştırmanın örneklemini Edirne ili merkezinde bulunan bir devlet okulu ile bir özel okulda bulunan basit rastgele örnekleme yöntemi ile seçilen 78 öğrenci oluşturmaktadır. Araştırmada veriler araştırmacılar tarafından hazırlanan genel bilgi formu ve Etkinlik Tercih Formu ile toplanarak SPSS 17 programı kullanılarak çözümlenmiştir. İki yönlü vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Special individuals are also members of the society and these individuals have right to take education such as people showing typical development. These individuals those will take the education, getting along with their peers with typical development will impact positively on their developments (Çetrez İşcan, Fazlıoğlu, Parlak, 2014). Considering the historical process in educational view, the first education taking environment of individuals who need special education were boarding/day care private schools.…”
Section: Introductionmentioning
confidence: 99%
“…Special individuals are also members of the society and these individuals have right to take education such as people showing typical development. These individuals those will take the education, getting along with their peers with typical development will impact positively on their developments (Çetrez İşcan, Fazlıoğlu, Parlak, 2014). Considering the historical process in educational view, the first education taking environment of individuals who need special education were boarding/day care private schools.…”
Section: Introductionmentioning
confidence: 99%
“…When the studies were reviewed there were studies showing that students without special needs had positive attitudes (Ozan-Bulduk, 2014) and negative attitudes (Ayral et al, 2015;Turhan, 2007) towards inclusion implementations. Some studies showed that the education background of parents of students without special needs did not have any effect on the attitudes of their children (Ayral et al, 2015;Çetrez-İşcan, Fazlıoğlu and Parlak, 2015) whereas others found positive effects of education background of parents on their children's attitudes towards inclusion implementation (Gümüş and Tan, 2015;Ozan-Bulduk, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Literatürde disleksi üzerine yapılan araştırmalara göre disleksinin iki farklı türü olduğu vurgulanmaktadır. Bunlar (Şenel-Günayer, 1998;Ercan, 2001): a. Gelişimsel Disleksi:…”
Section: Introductionunclassified
“…Bireyin daha önceden herhangi bir beyin hasarına rastlanmamış olmasına karşın, okumanın öğretilmesi sırasında fark edilen ve bireyin eğitim hayatı sürecinde karşı karşıya olduğu güçlüktür. Kuramlara bakıldığında, genel olarak dil ile alakalı bir sorun olarak düşünülen gelişimsel disleksinin, görsel algıyla alakalı bir problem değil de işitsel ve kısa süreli bellekle alakalı bir problem olduğu düşünülmektedir (Ercan, 2001). Yani gelişimsel disleksi yeterli zekaya sahip olmalarına rağmen okumayı öğrenmekte zorluk yaşarlar görsel algıyla alakalı bir problem yoktur okumadaki güçlük dil gelişimi ile alakalıdır.…”
Section: Introductionunclassified